2011
DOI: 10.1007/s11172-011-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

Dry reforming of methane on porous membrane catalytic systems

Abstract: A method of high performance dry reforming of methane into syngas at temperatures below 650 °C on membrane catalytic systems was proposed. The membrane catalytic systems consist of porous inorganic membrane supports, prepared by self propagating high tempera ture synthesis and modified by nanosized metallocomplex components, which are uniformly distributed inside membrane pores. The influence of the composition of the supported active components, temperature, and flow rate on the activity and selectivity of СН… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The carbon dioxide conversion of methane (CDCM) belongs to the most promising methods in demand for natural gas process ing. In a number of studies [5][6][7], it was found that the implementation of this reaction in a mambrane reac tor contator and a membrane reactor distributor with the use of porous membrane catalysts makes it possible to increase the degree of conversion, the selectivity, and the rate of process. A number of compounds (WC, Mo 2 C, and (La-Ce)-MgO-TiO 2 /Ni-Al), which do not contain expensive platinum group metals, can be used as active components.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon dioxide conversion of methane (CDCM) belongs to the most promising methods in demand for natural gas process ing. In a number of studies [5][6][7], it was found that the implementation of this reaction in a mambrane reac tor contator and a membrane reactor distributor with the use of porous membrane catalysts makes it possible to increase the degree of conversion, the selectivity, and the rate of process. A number of compounds (WC, Mo 2 C, and (La-Ce)-MgO-TiO 2 /Ni-Al), which do not contain expensive platinum group metals, can be used as active components.…”
Section: Introductionmentioning
confidence: 99%
“…The first peak at 450 C, according to the literature data, corresponds to the reduction of nickel oxide and the transition of Ni 2+ O to Ni 0 by reaction (3). The second and third peaks in the temperature range from 700 to 900 C are related to the reduction of cerium oxide (Ce 4+ to Ce 3+ ) by reaction (4 The calculation of the relative content of the oxide phases of metals on the surface of the studied sample 17 According to the literature data, the peak appeared in the temperature range 750-900 С is caused, most likely, by the reduction of manganese oxide (Mn 3+ 2 O 3  Mn 2+ O) 18 (Fig. 9).…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7] The MCS samples represent thermally stable (>1000 С) porous (porosity ~40%) ceramic membrane supports with the finger configuration and 130 mm in length with an external dia meter of 15 mm and a wall thickness of 4 mm ( Fig. 1) prepared from highly dispersed powders Ni(86.4%)-Al(13.6%) by the SPHTS method 10 and modified by the presence of the metal oxide catalysts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It goes in the same direction as the possibility of using porous inorganic-membrane supports modified with nanosized metallocomplex components, distributed into the membrane pores (Tsodikov et al, 2011). There are still some gaps of knowledge to fill, especially in terms of deposition techniques, because the main problems with this kind of system are associated with the fouling, due to solid carbon.…”
Section: Membrane Reactors For Methane Dry Reformingmentioning
confidence: 99%